2021
DOI: 10.1088/1755-1315/788/1/012204
|View full text |Cite
|
Sign up to set email alerts
|

The development of intensive beef cattle farming system in North Sulawesi with strategy management concept approach

Abstract: Beef cattle production in North Sulawesi needs to be increased because its growth was very slow, unable to keep up with the rate of consumer demand. The intensive system approach to beef cattle development was intended to increase production by increasing the ability or optimizing the productivity of the available production factors, where the current conditions for beef cattle development in North Sulawesi were generally maintained traditionally (extensively). This study aimed to obtain the concept of a long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…In addition, system maintenance and needs relative feed easy [8] will help the women in the village more productive for managing effort cattle chicken local as effort part-time family. As a result [9], the study confirmed that the population of free-range or free-range chickens in Minahasa Regency continues to increase. Though there is no definite data on the size of the population.…”
Section: Introductionsupporting
confidence: 63%
“…In addition, system maintenance and needs relative feed easy [8] will help the women in the village more productive for managing effort cattle chicken local as effort part-time family. As a result [9], the study confirmed that the population of free-range or free-range chickens in Minahasa Regency continues to increase. Though there is no definite data on the size of the population.…”
Section: Introductionsupporting
confidence: 63%
“…The three rearing systems were intensive, semi-intensive, and extensive. An intensive system is when cattle are kept in enclosures full time to facilitate feeding, reproduction activity, and monitoring of health and security, as well as allow less labor (Baba et al, 2014;Kalangi et al, 2021). A semi-intensive system allows animals to be herded in pastures during the day and kept in enclosures at night (Pugliese et al, 2021).…”
Section: Profiles Of Cattle Rearingmentioning
confidence: 99%
“…In Indonesia, livestock rearing systems mostly involve semi-intensive grazing and extensive systems [8]. Semi-intensive systems tend to align better with animal welfare compared to intensive systems [9].…”
Section: Introductionmentioning
confidence: 99%